A quality improvement initiative to optimize dosing of surgical antimicrobial prophylaxis. Issue 7 (21st March 2017) - Caruso, Thomas J.; Wang, Ellen; Schwenk, Hayden T.; Scheinker, David; Yeverino, Calida; Tweedy, Mary; Maheru, Manjit; Sharek, Paul J.
Summary: Background: The risk of surgical site infections is reduced with appropriate timing and dosing of preoperative antimicrobials. Based on evolving national guidelines, we increased the preoperative dose of cefazolin from 25 to 30 mg·kg −1 . This quality improvement project describes an improvement initiative to develop standard work processes to ensure appropriate dosing. Aims: The primary aim was to deliver cefazolin 30 mg·kg −1 to at least 90% of indicated patients. The secondary aim was to determine differences between accuracy of cefazolin doses when given as an electronic order compared to a verbal order. Methods: Data were collected from January 1, 2012 to May 31, 2016. A quality improvement team of perioperative physicians, nurses, and pharmacists implemented a series of interventions including new electronic medical record order sets, personal provider antibiotic dose badges, and utilization of pharmacists to prepare antibiotics to increase compliance with the recommended dose. Process compliance was measured using a statistical process control chart, and dose compliance was measured through electronic analysis of the electronic medical record. Secondary aim data were displayed as percentage of dose compliance. An unpaired t ‐test was used to determine differences between groups. Results: Between January 1, 2012 and May 31, 2016, cefazolin was administered to 9086 patients. The mean compliance of cefazolin at 30 mg·kg −1 from May 2013 to March 2014 was 40%, which prompted initiation of this project. From April 2014 to May 2016, a series of interventions were deployed. The mean compliance from September 2015 to May 2016 was 93% with significantly reduced variation and no special cause variation, indicating that the process was in control at the target primary aim. There were 649 cefazolin administrations given verbally and 1929 given with an electronic order between October 1, 2014 and May 31, 2016. During this time period, the rate of compliance of administering cefazolin at 30 mg·kg −1 was significantly higher when given after an electronic order than when given verbally, 94% vs 76%. Conclusion: This comprehensive quality improvement project improved practitioner compliance with evidence‐based preoperative antimicrobial dosing recommendations to reduce the risk of surgical site infections. Abstract :